Pengelolaan Wakaf Produktif di Kuwait Pembelajaran bagi Pengembangan Wakaf di Indonesia - Siska Siska (Jurnal Ekonomi KIAT, 2019)
Waqf is one of the ways of distributing welfare to the community. The continuity of the benefits of waqf is made possible by the enactment of the types of productive waqf established to support religious activities, compensation, education, and public facilities. Implementation of waqf in Indonesia especially productive waqf still faces various obstacles. Various waqf practices in other countries that are considered successful in managing productive waqf need to be a lesson for Indonesia, one of which is the application of productive waqf in Kuwait. This study is a theoretical study of productive waqf as well as a case study of the application of productive waqf in Kuwait which is considered successful. The development of waqf in Kuwait has passed a long stage (seven stages) from waqf management by the community (pre-1921 AD) until the SekjendWakaf (pre-1993 M). The types of waqf in Kuwait are also very diverse such as health endowments, water, public, investment endowments and so on. Kuwait has also implemented very good waqf governance with the establishment of the Awqaf Public Foundation (KAPF) in 1993. The existence of the KAPF is very influential in the development of waqf in Kuwait. The increase in waqf income for 16 years has tripled. Likewise, with the development of capital assets, there is a very significant increase.